Analysis of multiple genetic loci reveals MPDZ-NF1B rs1324183 as a putative genetic marker for keratoconus. Issue 12 (12th July 2018) - Wang, Yu Meng; Ma, Li; Lu, Shi Yao; Chan, Tommy Chung Yan; Yam, Jason C S; Tang, Shu Min; Kam, Ka Wai; Tam, Pancy O S; Tham, Clement C; Young, Alvin L; Jhanji, Vishal; Pang, Chi Pui; et al.
Abstract : Objective: To investigate the associations between 16 single-nucleotide polymorphisms (SNPs) in 14 genetic loci and keratoconus in an independent Chinese cohort. Methods: This cross-sectional, case-control association study included a Chinese cohort of 133 patients with keratoconus and 371 control subjects. In a recent meta-analysis study, we identified association of 16 SNPs in 14 gene loci with keratoconus. In this study, we genotyped these 16 SNPs in all the patients and controls and analysed their association with keratoconus, its clinical severities and progression profiles. We also analysed the genotype-phenotype correlation between individual SNPs and steep keratometry, flat keratometry (Kf), average keratometry (Avg K) and best-fit sphere diameter (BFS) of the anterior and posterior corneal surface. Results: Among the 16 selected SNPs, rs1324183 in the MPDZ-NF1B locus showed a significant association with keratoconus (OR=2.22; 95% CI 1.42 to 3.45, p=4.30×10 –4 ), especially severe keratoconus (OR=5.10, 95% CI 1.63 to 15.93, p=0.005). The rs1324183 A allele was positively associated with anterior Kf (p=0.008), anterior Avg K (p=0.017), posterior Kf (p=0.01) and negatively associated with apex pachymetry (p=0.007) and anterior BFS (p=0.023) in keratoconus. The other 15 SNPs had no significant association with keratoconus or genotype-phenotype correlations. Conclusions: This study confirmed the association of SNP rs1324183 in MPDZ-NF1B with keratoconus and revealed the association of this SNP with keratoconus severity and corneal parameters. It is thus a putative genetic marker for monitoring the progression of keratoconus to a severe form and facilitating early intervention.